2004
DOI: 10.1111/j.1600-0501.2004.00987.x
|View full text |Cite
|
Sign up to set email alerts
|

Histologic findings at augmented bone areas supplied with two different bone substitute materials combined with sinus floor lifting

Abstract: This case report is focused on the histologic findings of bone tissue supplied with two different hydroxyapatites (HAs) used for maxillary sinus floor grafting in the same patient after various healing intervals. An insufficient unilateral sinus floor grafting with Bio-Oss biomaterial was followed by an additional grafting procedure with Algipore biomaterial performed 4 years later. Bone samples obtained during second-stage dental implantation contained the interesting combination of Bio-Oss, a bovine anorgani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
0
8

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 13 publications
6
60
0
8
Order By: Relevance
“…From our point of view some authors overvalue the importance of the surface area of bioceramics in regards to the biological behaviours [34]. For example the bovine derived HA ceramics show a very high surface area based on nanopores but in vivo they can be characterized as non resorbable [27,35]. This fact supports our assumption, that nanopores play a minor role for bone resorption and remodelling because nanopores are not accessible for bone cell ingrowth.…”
Section: Discussionsupporting
confidence: 86%
“…From our point of view some authors overvalue the importance of the surface area of bioceramics in regards to the biological behaviours [34]. For example the bovine derived HA ceramics show a very high surface area based on nanopores but in vivo they can be characterized as non resorbable [27,35]. This fact supports our assumption, that nanopores play a minor role for bone resorption and remodelling because nanopores are not accessible for bone cell ingrowth.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, the natural macroporous HA ceramic (C Graft™/ Algipore ® ), calcifi ed from red algae (Corallina offi cinalis), with known mechanical and physicochemical properties was used. This material has been proven to have biocompatible properties as a bone graft substitute in vivo [Ewers and Schumann, 1994;Schopper et al, 2003;Ewers et al, 2004]. In vitro studies showed that this material supports the proliferation and differentiation of human osteoblast-like cells on its surface when grown in monolayer [Turhani et al, 2003[Turhani et al, , 2005a and in cellseeded three-dimensional bone composites [Turhani et al, 2005b, d].…”
mentioning
confidence: 99%
“…The calcium carbonate-based materials also have strong affinity for bone tissue attachment [12] and furthermore, are conducive for osteoblast proliferation and differentiation [13][14][15][16]. These properties make the coral skeleton a suitable candidate for delivering growth factors or bone marrow cells and have been used in numerous clinical applications for more than a decade [1,9,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 98%